Efektivitas Konseling Kelompok Dengan Pendekatan Rational Emotive Behavior Untuk Meningkatkan Self-Esteem Pada Remaja - Herman, Pebriani Yusnia; Karneli, Yeni; N, Netrawati (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Adolescence is a transitional period marked by significant physical, emotional, and social changes that can impact the development of self-esteem. During this period, adolescents often face challenges in finding their identity, which can lead to psychological issues such as anxiety and feelings of inferiority. Low self-esteem can affect emotional well-being and social behavior. Therefore, it is crucial to find effective approaches to improve their self-esteem. Method: This study uses a simple literature review method, which involves reviewing various relevant literatures on group counseling and Rational Emotive Behavior Therapy (REBT). Discussion: Self-esteem is defined as an individual’s assessment of their value and abilities, which influences various aspects of life, including academic achievement and social relationships. Adolescents often experience low self-esteem due to social pressures, especially through social media platforms like TikTok, which exacerbate feelings of inferiority. REBT, developed by Albert Ellis, can address this issue by replacing irrational thoughts with rational ones, enhancing self-confidence, and reducing anxiety. Group counseling based on REBT can help adolescents improve their self-esteem, enhance social relationships, and develop constructive coping skills to face life’s challenges.